FIGHT AMONG POLITICAL ACTORS ON PRINTED MEDIA AS PART OF GENERAL ELECTION HELD TO VOTE FOR REGENT OF BANGLI REGENCY IN 2010 - Ras Amanda Gelgel, Ni Made (E-Journal of Cultural Studies, 2014)
In the era of after reformation, Indonesia has developed rapidly enough in political sector and mass media freedom. In the local level such as in Bangli Regency, Bali Province, the fight among political actors on the printed mass media took place when the general election to vote for the regent was held. The general election which was held to vote for the regent was full of dynamism in which the candidates fought against one another on the longer mass media. The problems of the present study are as follows: (1) what was the fight among political actors on the printed media when the general election was held to vote the regent of Bangli Regency in 2010 like?; (2) the factors leading to it?; and (3) what was the impact and meaning of the fight among the political actors on the printed media? The theories used in the present study were the theory of discourse of relation of knowledge and power, the theory of the impact of media such as the agenda setting, the theory of framing, the theory of media text analysis, the theory of hegemony, and the theory of capital. The research method used was the qualitative approach with critical paradigm.  The forms of the fight among political actors took place in the arenas of news articles, advertorials, advertisements, and paid articles. The fight taking place in these arenas started from the fight for the self-image of the actors to the political issue. The factors leading to it was political factor, economic factor, and mass media. The fight among the political actors affected political sector, economic sector, and cultural sector. The fight among the political actors on the printed media contained pragmatic meaning of the media and political actors, the image, popular life style, and change of political culture in Bangli.
Keywords: printed media, politics, general election, political communication, political actors.